COMMUNITY-LED HEALTH PLANNING MODEL FOR VILLAGE HEALTH TEAM :A CASE STUDY IN INDONESIA: COMMUNITY-LED HEALTH PLANNING MODEL - Tasnim Tasnim (STIKes Mandala Waluya Kendari, 2020)
Background: An effective health planning is a root of success to cope with public health problems in the village. Communities in the village have resources to solve the problem. However, they do not have the skill to cope with their problem. This qualitative study is to analyze the process of community-led health program planning. Methods: This qualitative method using Participatory Rural Appraisal Approach which recruited village communities and government from April to August 2016 in Lambusa and Lebojaya Villages, Konda Sub-district in Southeast Sulawesi Province, Indonesia. Data analysis used interpretive analysis. Results: This study found that there were several steps to empower village communities to develop village health planning. Firstly, socialization about the process and establishing a Village Facilitator Team. Then, The VFT was be trained to increase their knowledge and skill about the village health program planning. The final step is a community meeting to identify the causes of illness and death and developing the village health program for dealing with the causes. Conclusion: community-led health planning process can be implemented in the village to increase the quality of the village health program, especially in the remote or village areas.